Wireless Powering System for Implantable Bio-Mems Sensor - Pavithra, S.; Sreeja, B. S.; John Wiselin, M.C.; Kamal, A. (Asian Journal of Science and Applied Technology, 2012)
The aim of this proposal is to design a wireless powering system for an Implantable Bio-MEMS Sensor which is used to power up the implanted sensor inside the human body. It is highly desirable due to obviation of batteries or piercing wirings. The implanted sensor is powered up it senses the measureable parameters in the human body and the sensed signals are transmitted to the receiver section that is kept outside the human body. RF powering relies on an inductively coupled electromagnetic link to wirelessly transmit RF power from an external unit to an implanted system. This technique has been widely used for biomedical implants. The system consideration including the inductive coupling and the circuit building blocks of power management are given.